Compartilhamento de responsabilidades harmônicas: análises, contribuições e proposições - Santos, Andréia Crico dos (2019)
Faced with the intensification of nonlinear elements connected to electric systems, at generation, transmission and distribution levels, new challenges emerge when one thinks about the best way to manage distortions to safe levels. In the literature there are challenging gaps in the context of establishing a reliable, robust and practical method for sharing of responsibilities between the parties that contribute to the distortions found in a particular bus. The present work intends to contribute to advances in this field of investigations. Initially, it seeks to consolidate an existing methodology, based on the use of dominant impedances to obtain the sharing of responsibilities. About this topic, definitive conclusions are obtained from detailed analyzes and this allows the safe and effective application of the process. As original propositions, two other methodologies focused on harmonic sharing are presented: one based on the injection of harmonic currents, and another based on the use of capacitor switching. Such procedures involve interventions and measurements at the point of interest for the assignment of responsibilities. By recognizing as a relevant proposal the possibility of performing actions in a certain bus and obtaining the responsibility percentages in another point, this work still proposes the methods for extrapolation of harmonic sharing. Within this purpose, procedures are developed, using again the philosophies of connection of dominant impedances, injection of harmonic currents and switching of capacitors. To support the propositions made, the theoretical foundations of all methodologies are described, and they are subjected to performance tests in terms of computational simulations and laboratory tests. The results obtained are promising and, thus, the propositions present the potential to contribute effectively to the scientific advances in the theme sharing of harmonic responsibilities.